Producing News Stories on the YouTube Platform by Mobile Journalists in Indonesia - Roswita Oktavianti; Sinta Paramita; Gregorius Genep Sukendro (Jurnal Ilmu Komunikasi, 2024)
Mobile journalism has been a mainstay in some news media outlets as audiences migrate to smaller screens for news. In response to the competitive media environment, organizations embrace mobile technology to expand the scope of their content. This article employs emerging perspectives as one of the organizational theory approaches. This study aims to determine the process behind news stories created by mobile journalists depending on their institution, the current circumstances, and technological advances. This study compares mobile journalists from two different news YouTube channels in Indonesia. Researchers collected data by observing news videos and interviewing news editors. The result showed that rules upheld by the media organizations would determine their productivity, the topic of news stories, and the quality of news sources. The COVID-19 pandemic has changed the news creation process as they had to work remotely. In addition, it is worth noting that mobile journalists must shoot and edit videos and have a multimedia mindset. This study suggests that a newsroom must have stricter rules and guidelines as it will be the main factor in producing news videos on YouTube channels. Journalists should also be prepared to adopt digital technology to cope with unprecedented situations.